COVID-19-associated nephritis: early warning for disease severity and complications? - Gross, Oliver; Moerer, Onnen; Weber, Manfred; Huber, Tobias B; Scheithauer, Simone (The Lancet (British edition), 2020)
SARS-CoV-2 uses the receptor ACE2 for cell entry, and podocytes express ACE2.1 Glomerular changes and nephritis-like histology have been described in postmortem samples from patients with COVID-19.2 Other zoonoses, such as some hantaviruses, cause nephrotic syndrome, which in turn induces cardiopulmonary syndrome.3,4 Complications of nephrotic syndrome are known to be similar to capillary leak syndrome, and preventive therapies are available.5 We recommend that patients with COVID-19 who have nephritis be carefully monitored for the following conditions: pulmonary interstitial oedema, due to severe fluid overload similar to nephrotic syndrome; immune incompetence, due to renal loss of immunoglobulins; circulatory insufficiency, due to hypalbuminaemia; poor drug response because of impaired plasma protein binding; and thromboembolic events due to antithrombin deficiency. In summary, the respiratory tract is the gateway for SARS-CoV-2 infection, but we postulate that COVID-19-associated nephritis, which can be easily screened for through a simple and inexpensive urine sample analysis, might help predict complications. If validated, we believe this tool could allow early anticipation of later need for ICU admission, improved allocation of patients for special therapies (eg, in clinical trials), and initiation of preventive strategies focused on capillary leak syndrome, including treatment that could save lives.